A review of psychostimulant-induced neuroadaptation in developing animals - Carrey, Normand (Neurosci Bull, 2011)
The effects of clinically relevant doses of commonly prescribed stimulants methylphenidate (MPH), d-amphetamine (d-AMPH), and dl-AMPH or mixed amphetamine salts (MAS) such as Adderall, on short- and long-term gene neuroadaptations in developing animals have not been widely investigated. In the present review, the effects of oral stimulant administration were compared with those of the subcutaneous or intra-peritoneal route. A selective set of studies between 1979 and 2010, which incorporated in their design developmental period, clinically relevant doses of stimulants, and repeated daily doses were reviewed. These studies indicate that neuroadaptation to chronic stimulants includes blunting of stimulated immediate early gene expression, sensitivity of younger (prepubertal) brain to smaller dosages of stimulants, and the persistence of some effects, especially behavioral neuroadaptations, into adulthood. In addition, oral amphetamines (MAS) have more profound effects than does oral MPH. Further animal developmental studies are required to understand potential long-term neuroadaptations to low, daily oral doses of stimulants. Implications for clinical practice were also discussed.